Transesophageal electrophysiology study in the diagnosis of dual atrioventricular nodal nonreentrant tachycardia. Issue 1 (30th March 2021) - Chen, Jing; Lin, Fan; Zuo, Ping; Li, Shixu; Lin, Li; Wang, Bei; Yang, XiaoYun
Abstract: "Double fire" is generally characterized by 1:2 atrioventricular conduction of sinus beats traveling down fast and slow pathways that result in double ventricular response. When this phenomenon repeats rapidly, dual atrioventricular nodal nonreentrant tachycardia (DAVNNT) occurs. We report a case of an irregular tachycardia with a comprehensive record that includes an electrocardiogram, a transesophageal electrophysiology study, and an intracardiac electrophysiology study. This is the first report of transesophageal electrophysiology study in the diagnosis of DAVNNT. A diagnosis of DAVNNT was deduced, and the patient was successfully treated with radiofrequency ablation of the slow pathway.